INFLUENCE OF SOCIAL SUPPORT TO HEALTH BELIEF ON PATIENTS DECREASE IN FUNCTION - Siwi Respati, Winanti; Tias Rangganis, Safira; M, Safitri; Prasetya, Adhita (International Journal of Psychosocial Rehabilitation, 2020)
Decreased kidney function has a growing number of sufferers each year. Treatment carried out and the risk of not doing treatment creates a burden for patients. In this disease, patients are required to always obey the doctor's advice or have health beliefs. One factor that influences one's health beliefs is social support. This study aims to determine the effect of social support on health belief in patients with decreased kidney function. This research is quantitative non-experimental with 100 research respondents. The sampling technique in this study was purposive sampling. Measuring social support was measured using a social support scale based on Sarafino's theory adapted from Gideon (2010) totaling 36 valid items with a reliability value of 0.920 and a health belief measuring instrument measured using a health belief scale based on the theories of Janz and Becker of Widyaningsih (2018) which was modified amounting to 25 items with a reliability value of 0.848. Simple linear regression test results obtained sig. (P) = 0,000 with a coefficient of +0.308 which means that the hypothesis is accepted that social support has a significant positive effect on health belief. The value of R 2 indicates social support influences health beliefs of 16.4% is influenced by other factors. Patients with decreased kidney function were predominantly having negative health beliefs of 51%. Gender and age have no relationship with the patient's health belief in decreased kidney function. Patients who have high health beliefs in this study were predominantly male and in late adulthood.